Enhancing the Electricity Generation and Nitrate Removal of Microbial Fuel Cells With a Novel Denitrifying Exoelectrogenic Strain EB-1 - Jin, Xiaojun; Guo, Fei; Liu, Zhimei; Liu, Yuan; Liu, Hong (Frontiers in Microbiology, 2018)
Microbial fuel cells (MFCs) have been tentatively applied for wastewater treatment, but the presence of nitrogen, especially nitrate, induces performance instability by changing the composition of functional biofilms. A novel denitrifying exoelectrogenic strain EB-1, capable of simultaneous denitrification and electricity generation and affiliated with Mycobacterium sp., was isolated from the anodic biofilm of MFCs fed with nitrate containing medium. Polarization curves and cyclic voltammetry showed that strain EB-1 could generate electricity through a direct electron transfer mechanism with a maximum power density of 0.84 ± 0.05 W m-2. Additionally, anodic denitrification, as a concurrent metabolism, was demonstrated with an efficient removal rate of 0.66 ± 0.01 kg N m-3 d-1 at a COD/N ratio of 3.5 ± 0.3. Importantly, voltage output was not negatively influenced by nitrate, indicating that the concurrent process of nitrate removal and electricity generation was a limitation of the electron donor rather than an inhibition of the system. Furthermore, various organic materials were successfully utilized as anode donors for strain EB-1, and demonstrated the exciting performances in terms of simultaneous denitrification and electricity generation. Mycobacterium sp. EB-1 thus expands the diversity of exoelectrogens and contributes to the potential applications of MFC for simultaneous energy recovery and wastewater treatment.